Produktivitas Jamur Merang (Volvariella volvaceae) pada Media Campuran Sekam dan Jerami Padi yang Ditanam dalam Baglog dan Keranjang - Irawati, Irawati; , Dra. Suparti M.Si (2017)
Rice husk is one result of the processing of rice that have the main content in the form of cellulose, so the rice husk can be used as a growing medium for mushroom. The purpose of this study to determine the effect of rice husk in a variety of weight media, the effect of planting baglog and basked, and rice husk media interaction in various weihgs by planting in basket on productivity baglog and mushroom. This study was prepared by a completely randomized design (CRD) with two factors and three replications. Factor 1 weight of rice husk: (S1) 125g, (S2) 250g, (S3) 375g, 500g S4. Factor 2 planting: (U) basket, (B) baglog. The parameters measured were the number of fruiting bodies and edible mushroom fruit body weight. Data were tested by ANOVA analysis of two paths. Based on the analysis of variance showed that the addition of different weights of rice husk media by planting in basket and baglog give effect to the amount of body weight of fruit and mushroom fruit body. The best treatment for a number of fruiting bodies is US1 ie 44,03 fruit, while the lowest was treatment BS4 of 6,63 units. The best treatment for body weight of the fruit is US0 is 630,0g, while the lowest treatment BS4 is 106,6g.